Design of a class-Ф inverter - Chen, Chen (Nanyang Technological University, 2024)
Wireless power transfer systems have been widely studied, especially in 13.56 MHz This dissertation presents a framework for modeling, analysis, and design a Class -Φ Inverter, a single switch topology with low switch voltage stress and fast transient. Building upon this foundation, a compensation topology was introduced to enhance the smoothness of the circuit’s output voltage and achieve load-independent characteristics. Subsequently, simulation analysis and verification were conducted using LTSPICE. The results show that Class Φ inverter with Series-Series(SS) compensation can improve the smoothness of the output waveform, have better filtering effect, and have a lower impact on the output voltage as the resistance changes.